The Position of Leivu - Kallio, Petri (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2021)
Leivu has generally been connected with Võro and especially its Hargla dialect. However, this classification has always been based on superficial synchronic similarities rather than a rigorous diachronic analysis. Instead, closer examination shows that Leivu is the earliest offshoot of South Estonian and that its similarities with Hargla Võro can better be explained by their geographical proximity. Kokkuvõte. Petri Kallio: Leivu asend. Leivut on üldiselt ühendatud võro keelega ja eriti Hargla murrakuga. Paraku need klassifikatsioonid on alati tuginenud pindsete sünkroonsete sarnasuste arvestamisele, mitte rangele diakroonilisele analüüsile. Siinne lähem vaatlus näitab, et leivu on esimesena lahknenud lõunaeesti keeleühtsusest ning selle sarnasusi Hargla võro keelega saab seletada pigem geograafilise lähedusega.